Pengembangan Soal Matematika Berkarakteristik TIMSS Tipe Pemecahan Masalah pada Topik Geometri Pengukuran Volume Kubus dan Balok Kelas VIII - Pratiwi, Ika; Zulkardi, Zulkardi; Susanti, Ely (Jurnal Elemen, 2016)
This research aims to produce a TIMSS characterized math problems that are valid and reliable. The method of this research is Design Research. The sample of this study were 31 students of SMP Negeri 1 Inderalaya. The procedure of this study through the stages of Preliminary Evaluation and Formative Evaluation. Based on the results obtained 7 of TIMSS characterized with characteristics (1) using real-life contexts, (2) using characteristics of TIMSS, and (3) the type of problem-solving that problem logically and empirically validÂ  and reliable. Valid logically be fulfilled from the results of the assessment validator, where the validator comment on the terms of the content, construct, andÂ  language. Valid empirically criteria for both internally for items validity and externally for the whole items validity. Items also expressed reliable with a high level of confidence as the test instrument through items with the analysis result reliability coefficient of 0,703.